2009
DOI: 10.1007/s11661-009-9810-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Defects, Surface Irregularities, and Quenched-In Defects on Corrosion of Zr-Based Metallic Glasses

Abstract: X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) revealed a fully amorphous structure for as-cast bulk metallic glass (BMG) and melt-spun ribbons of Zr 52 Ti 6 Al 10 Cu 18 Ni 14 prepared by copper mold casting and the melt-spinning technique, respectively. For melt-spun ribbons, the wheel-side surface contained a higher concentration of quenched-in defects (air pockets), whereas surface irregularities were noticed in the air side. Fluctuation microscopy indicated more medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Previous surface analytical studies revealed that surface films on Zr-based metallic glasses formed naturally in air or under electrolyte exposure consist mostly of Zr oxides and contain additionally small amounts of other valve metals (in their oxide states), e.g., Al, Nb, and Ti. 4,[17][18][19]21,37 Accordingly, the similar E corr values of the glassy alloys studied here are attributed to their similar surface chemistry, i.e., consisting mostly of Zr oxides. Upon further increase in the potential (see Fig.…”
Section: A Pitting Susceptibility and Repassivation Abilitysupporting
confidence: 61%
“…Previous surface analytical studies revealed that surface films on Zr-based metallic glasses formed naturally in air or under electrolyte exposure consist mostly of Zr oxides and contain additionally small amounts of other valve metals (in their oxide states), e.g., Al, Nb, and Ti. 4,[17][18][19]21,37 Accordingly, the similar E corr values of the glassy alloys studied here are attributed to their similar surface chemistry, i.e., consisting mostly of Zr oxides. Upon further increase in the potential (see Fig.…”
Section: A Pitting Susceptibility and Repassivation Abilitysupporting
confidence: 61%
“…In addition, most MGs possess a natural passive oxide layer that gives them an additional good corrosion resistance. A recent work by Vishwanadh et al 5 on Zr-based BMG also pointed out a strong influence of the sample surface morphology or irregularities on corrosion. However, several recent investigations on bulk metallic glasses ͑BMGs͒ made of Zr-based metals demonstrated prevalent pitting corrosion, which is most notorious in limiting applications.…”
Section: Correlation Between Corrosion Performance and Surface Wettabmentioning
confidence: 92%
“…It was suggested that surface topological defects like air pockets played an important role on the corrosion. 7) Not immersion in solution but keeping in air, the formation of ZrO 2 layers at the surface was reported for a-Zr 40 Cu 60 . 8) As mentioned above, the corrosion resistance of ZrCubase amorphous alloys is not so high in the solutions containing the halogen ions more than $10 mM.…”
Section: Introductionmentioning
confidence: 96%